Dilema Sistem Return to Seller (RTS) dan Integrasi Data Lintas Platform terhadap Kinerja Kurir (Studi Kasus pada J&T Express DC_Gubeng) - Maya Susanti; Hesti Cahya Adistia; Jennie Amanda; Tan Evan Tandiyono (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
The Cash on Delivery (COD) system remains a popular choice for consumers as it guarantees a sense of security in transactions, but this method creates high operational complexity for J&T Express. The main problems that frequently occur in the field include unilateral payment rejections by consumers and high rates of returns or Return to Sender (RTS). This qualitative case study aims to evaluate the effectiveness of the Management Information System at J&T Express DC_Gubeng, Surabaya, through direct observation and in-depth interviews with supervisors, admins, and field couriers. Field findings indicate that the problematic address validation feature has not been automatically implemented in the system, but still relies on courier experience and manual confirmation via WhatsApp before the goods are delivered. The biggest technical obstacle stems from the misalignment of upstream API integration with the e-commerce platform, which triggers a loophole for cross-platform fake receipt manipulation (cross-marketplace fraud). In addition, the RTS procedure, which requires three physical delivery attempts, wastes the courier's effective working time (idle time). Delays in synchronizing order cancellation data from the application have also been shown to reduce the achievement of the courier's digital KPI targets. On the positive side, GoPay's digital wallet-based financial interconnection has proven highly reliable in maintaining accurate real-time cash-on-delivery (COD) reporting and reducing daily financial disputes. As a recommendation, J&T Express should optimize upstream data integration with e-commerce partners and relax package return regulations to achieve operational efficiency.